Evolution and Phylogeny of Mesozoa - Drábková, Marie (Jihočeská univerzita, 2022)
This thesis focuses on the phylogenetic position of Mesozoa (Orthonectida and Dicyemida) based on phylogenomics, and on dicyemid life-history traits revealed by molecular methods used in population genetics. The thesis is introduced by the review of biology of both groups, complemented by up to now development of views on their phylogenetic position and notes concerning the study of the population structure of marine invertebrates. The introduction is followed by a study focusing on the phylogenetic position of Mesozoa, a comparison of population structure between the cephalopod host and its dicyemid parasite, and a case study of dicyemid parasite infrapopulation. The thesis wraps up with a review on cephalopod parasites and a summary.
Evolution and Phylogeny of Mesozoa
Keywords: Mesozoa; Dicyemida; Orthonectida; Phylogenomics; Population genetics; Marine biology; Parasites